Impact of information and communication technology on the gross domestic product - guelmine, hichem; bousaha, mohamed lakhdhar (Journal of Social Sciences and Humanities, 2023)
this study highlights the impact of ICT on GDP as represented by Algeria's per capita GDP growth rate through a standard study for the period 1995-2020. In order to achieve the goal, the self-declining methodology for slowing time gaps has been used (ARDL), based on the independent variables of the IT index, Population growth, inflation and Algerian per capita representation of economic growth as a subordinate variable. Through this study, we have reached a series of findings, notably that the increase in the ICT index will result in a decrease in Algeria's per capita GDP. The high rate of population growth also led to a decline in Algeria's per capita GDP, and the study concluded a series of important recommendations.